2011
DOI: 10.1111/j.1365-2958.2011.07809.x
|View full text |Cite
|
Sign up to set email alerts
|

Arginine catabolic mobile element encoded speG abrogates the unique hypersensitivity of Staphylococcus aureus to exogenous polyamines

Abstract: Polyamines, including spermine (Spm) and spermidine (Spd), are aliphatic cations that are reportedly synthesized by all living organisms. They exert pleiotropic effects on cells and are required for efficient nucleic acid and protein synthesis. Here, we report that the human pathogen Staphylococcus aureus lacks identifiable polyamine biosynthetic genes, and consequently produces no Spm/Spd or their precursor compounds putrescine and agmatine. Moreover, while supplementing defined medium with polyamines general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
177
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(180 citation statements)
references
References 51 publications
3
177
0
Order By: Relevance
“…Triolein, a triglyceride composed of glycerol and three molecules of oleic acid (C 18:1 cis-9) was evaluated first. Triolein is similar to trilinolein in the sense that the chains of the fatty acids esterified to glycerol are the same length (C 18 ), yet in trilinolein the fatty acid chains are diunsaturated (C 18:2 ), while they are monounsaturated (C 18:1 ) in triolein. A significant delay in growth was observed in the presence of triolein compared to when the cells were grown in TSB alone, although the delay was reproducibly not as severe as when the cells were grown in the presence of trilinolein (Fig.…”
Section: Sal2 Hydrolyzes Trilinolein To Linoleic Acid the Pnpp-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…Triolein, a triglyceride composed of glycerol and three molecules of oleic acid (C 18:1 cis-9) was evaluated first. Triolein is similar to trilinolein in the sense that the chains of the fatty acids esterified to glycerol are the same length (C 18 ), yet in trilinolein the fatty acid chains are diunsaturated (C 18:2 ), while they are monounsaturated (C 18:1 ) in triolein. A significant delay in growth was observed in the presence of triolein compared to when the cells were grown in TSB alone, although the delay was reproducibly not as severe as when the cells were grown in the presence of trilinolein (Fig.…”
Section: Sal2 Hydrolyzes Trilinolein To Linoleic Acid the Pnpp-basedmentioning
confidence: 99%
“…Recent studies have indicated that the emergence and rapid geographic spread of USA300 were due, at least in part, to its enhanced ability to persist on human skin, which was attributed to a mobile genetic element that uniquely confers resistance of USA300 to toxic polyamines encountered on the skin, to which all other strains of S. aureus are sensitive (18,19). Nevertheless, S. aureus as a species is capable of colonizing humans and must also cope with other innate defense mechanisms of the skin, the foremost of which include the production and secretion of sebum by the sebaceous glands (20,21).…”
mentioning
confidence: 99%
“…Spermidine and putrescine are notably essential for virulence in Salmonella gallinarum (62) and in P. aeruginosa, where spermidine is necessary for expression of the type III secretion system that delivers virulence proteins into eukaryotic cells (63). This differs from S. aureus, which cannot produce spermine or spermidine or the precursors agmatine and putrescine (64). Guanosine was lower.…”
Section: Discussionmentioning
confidence: 85%
“…They are found in almost all living organisms [4]. Polyamines are produced by nearly all bacteria, with rare exceptions such as Staphylococcus aureus strains to which some polyamines, namely spermidine and spermine, are toxic as they lack polyamine-detoxifying enzymes [5]. The most common bacterial polyamines are putrescine and spermidine [6].…”
Section: Polyaminesmentioning
confidence: 99%